THE USE OF VIDEO AS AN INSTRUCTIONAL MEDIA BY TEACHER IN TEACHING SPEAKING: A Descriptive Study of One Senior High School in West Bandung Regency - Pratiwi, Annisa Nur (2016)
This research was aimed at investigating way teacher used video as instructional media in teaching speaking and the problems the teacher encountered during the utilization of video and how to overcome the problems. This study was conducted at a senior high school in West Bandung Regency. The qualitative method was designed to collect the data. Therefore, classroom observation, interview, and document analysis were employed in this research. The results of the study indicate that the utilization of video needed two basic steps, namely steps in selecting educational video and steps in utilizing the video. Practical techniques for video viewing activity, determination of video in a lesson, procedure in showing video, and educational values of using video are essential in utilizing video as the instructional media. In meantime, teacher encountered problems during the selection and utilization of video. To overcome the problems in video selection process, teacher involved school facilities and technician's help. As for problems in utilization of video, teacher prepared backup media and backup activity to overcome the problems. Keywords: Video, instructional media, video selection, video utilization, problem solving in video selection and utilization, teaching speaking Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana guru menggunakan video sebagai media instruksional dalam pengajara Speaking dan permasalahan yang dihadapi selama penggunaan video dan bagaimana solusinya untuk permasalan tersebut. Penelitian ini telah diadakan di salah satu sekolah menengah atas yang ada di Kabupaten Bandung Barat. Metode deskriptif qualitatif digunakan dalam pengumpulan data. Maka dari itu, observasi kelas, wawancara, dan analisis dokumen menjadi instrument yang dipakai dalam peneletian ini. Hasil penelitian menunjukkan bahwa penggunaan video meliputi dua tahapan penting, yaitu tahap memilih video dan tahap penggunaan video di dalam kelas. Tehnik penayangan video, kedudukan video di dalam pembelajaran, dan prosedur penampilan video menjadi bagian yang penting dalam penggunaan video. Sementara itu, guru juga mengalami beberapa permasalahan selama pemilihan dan penggunaan video di dalam kelas. Dalam menyelesaikan permasalahan yang ditemui selama pemilihan video, guru memberdayakan fasilitas sekolah dan bantuan staf IT sekolah. Sedangkan untuk permasalahan yang ditemui guru selama penggunaan video di dalam kelas, guru mempersiapkan media dan kegiatan pengganti sebagai solusinya. Kata Kunci: video, media instruksional, pemilihan video, penggunaan video, penyelesaian masalah dalam pemilihan dan penggunaan video